U–Th Dating of the RAT Speleothem from Menorca Island (387–209 ka) - Judit Torner; Isabel Cacho; Heather M Stoll; Ana Moreno; Joan O Grimalt; Francisco Javier Sierro; Joan J Fornós; Hai Cheng; R Lawrence Edwards (PANGAEA, 2025)
This dataset comprises U-Th dating results from the RAT speleothem. The data were used to reconstruct past climate variability in the western Mediterranean region over the interval 387 to 209 ka, encompassing several glacial terminations (TIV, TIII, and TIIIa). The speleothem was collected in winter 2011 from Murada Cave, located on Menorca Island (39°57'58''N; 3°57'53''E). Element isolation was performed according to Shen et al. (2002) and Cheng et al. (2009). U-Th dating was conducted using a multi-collector inductively coupled plasma mass spectrometer (MC-ICP-MS) with parallel ion-counting (Finnigan Neptune) at the University of Minnesota and Xi extquotesinglean Jiaotong University. Age-depth models were calculated with the StalAge package in R (Scholz and Hoffmann, 2011).